Pawai Hari Santri Dalam Rangka Memperingati Hari Santri Nasional Yang Dilaksanakan Oleh SDN 2 Sambirejo Di Desa Sambirejo Kabupaten Trenggalek - Gerry Ironika (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
The commemoration of National Santri Day on October 22nd is an important occasion to emulate the struggles and Indonesian values ​​inherited from Islamic scholars and students. SDN 2 Sambirejo in Sambirejo Village, Trenggalek Regency, capitalized on this momentum by holding a Santri Day Parade as a way of preserving local wisdom and instilling religious values ​​and nationalism in students. This research is motivated by the importance of understanding how parades can strengthen students' character while strengthening school-community ties. The purpose of this study is to describe the implementation of the Santri Day Parade, identify its values, and analyze its role in shaping students' religious and national character. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that the parade was met with high enthusiasm from students, teachers, and the community, and instilled religious values, togetherness, a love of Islamic traditions, and a sense of nationalism. Furthermore, this activity served as an effective educational tool for preserving local culture and strengthening the relationship between the school and the community.